Physical abuse during pregnancy : an experience of 139 cases (Northern International Medical College Journal, 2015)
Objective : To assess pattern and proportion of physical abuse during pregnancy in relation to socio demographic characteristics of abused women.Material & Methods : A descriptive type of cross sectional study was conducted in RADDA-MCH-FP Center, Mirpur-10, Dhaka during January to July 2011. A total of 139 pregnant women of reproductive age group (15-45) years who visited for antenatal check up were selected purposely. Data were collected through face to face interview using pretested structured questionnaire.Results : Socio demographic characteristics of respondents revealed that mean age 22.20 ± 39 years and husbands mean age 28.57 ± 5.39 years. Highest number of respondents education upto SSC level (49.6%). 74.8% were housewife; socio economic status was lower middle class, 18.7% had history of dowry. The proportion of physical abuse during pregnancy was 31.6%. Among them 15.83% had mixed type of abuse. Highly significant association was found with dowry (p 0.00) and planed pregnancy (p 0.006). A statistically significant association was found between respondents education level and physical abused (p